The Concept of God's Omnipotence from a Theological Perspective and Its Contextualization - Wellem Saputra Munthe; Pintor Marihot Sitanggang (Jurnal Penelitian Medan Agama, 2026)
This article discusses the theological perspective and contextualization of the present, omnipotence is no longer interpreted as merely miraculous intervention, but rather as God's love, care, and active presence in the real struggles of humanity in the world. This concept emphasizes that God is not only a creator who withdrew after creating the world, but also a person who continues to be present and involved in every aspect of the lives of His creation. This study explains how God's immanent and transcendent omnipotence is understood in the perspective of systematic theology by using the lens of Martin Luther's teachings and then explaining its contextualization in the HKBP Confessions of 1951 and 1996. The conclusion of this article states that there is an interaction and relationship between God and humans. This relationship begins with the person of God who first introduces himself to humans and gives humans the opportunity to make decisions according to the free will they already have.